The Relationship between Organizational Citizenship Behavior (OCB) and Innovative Work Behavior (IWB) - Ismail, Nur Zahara; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2021)
Nowadays, company need a good strategy by including innovation which require Innovative Work Behavior (IWB) to boost company performance, but manager lack of information on how to innovate. However, Organizational Citizenship Behavior (OCB) as a voluntary work behavior may influence the company performance through innovation. This study has been conducted due to an issue of less innovative employees in manufacturing sector as compared to service sector. So, the purpose of this research is to investigate the level of OCB and IWB among employees in manufacturing sector in Penang. This study also attempts to address the relationship between OCB and IWB. The questionnaire has been distributed using online platform. The study employed a random sampling techniques. Descriptive analyses have been used to find out the result. The finding shows the high level of OCB and IWB among employees in manufacturing sector. Other than that, correlation analysis that has been conducted resulted in a moderate positive relationship between OCB and IWB. Therefore, there is a relationship between OCB and IWB. Furthermore, five dimension of OCB proved to be the strong behavior to develop all stages of IWB. The result from this study suggest manufacturing sector can focus on employees innovation in line with the practice of OCB from employees. For future studies, it can be carried out in a longer period to achieve more accurate result.